Fashion and Ergonomic Design: Aspects that Influence the Perception of Clothing Usability - Neves, Érica P. das [UNESP]; Brigatto, Aline C. [UNESP]; Paschoarelli, Luis C. [UNESP] (Elsevier, 2015)
The relevant issues about clothing have been increasing in recent times. The increase number of consumers and users that search for differentiated and appropriate products to their needs and expectations is impacting on the design stages as well as on manufacturing process. Thus the understanding of specified segments of consumers and users emerges as a competitive strategy that is favourable to the development of products that are adequate and satisfactory to different individuals. Regarding the fashion context, the clothing product provides to the emotional level channels of signification and subjective identification. Considering the direct contact between clothing and user, the information about anthropometric biomechanical and ergonomic are of extreme relevance for the development of modelling that are appropriated to different needs of different segments of users.
Keywords: Anthropometric; Ergonomic Design; Fashion; Usability